15 Exploration of the Cavernous Sinus Is Effective During Transsphenoidal Surgery for Pituitary Adenoma (Controversies in Skull Base Surgery, 2019)
Parasellar invasiveness into the cavernous sinus is the most important prognostic factor for incomplete resection and recurrence of pituitary adenomas. Pituitary adenomas extending and invading the space of the cavernous sinus represent a different entity of tumors with higher growth rates, and extension into the inferior compartment plays a particularly important role. However, surgical resection of pituitary adenoma tissue extending/invading the space of the cavernous sinus is feasible and can improve the rate of endocrine remission, with a low rate of complications.
Keywords: pituitary adenoma; cavernous sinus; parasellar; endocrine remission; gross total resection; extended approach